Nano-shield a feasibility study - Castro, Rowell D. G.; Fajardo, Andrew Ale S.; Jose, Kevin Bryan C.; Lorenzo, Simon Anthony D. (College of Engineering, 2013)
Nanomaterial research has been one of the forefronts of scientific research for the past decade. Despite its recent discovery, nanotechnology has already been proven to have numerous applications in different fields such as medicine and manufacturing. The growth of nanomaterial research and technology is so fast that that it has been forecasted that most of the things people will be using in the near future will already consist of nanomaterials. The Nano-Shield is a product which utilizes the power of nanotechnology. It is a liquid solution which consists of water, epoxy resin, and Sn02 (Tin (IV) Oxide) nanomaterials. The product has anti-heat and anti-bacterial properties. Once the solution is applied to glass, the glass is able to limit the heat accumulation within the room or vehicle. Furthermore, bacterial levels in the room can also be reduced. There are two primary target markets which the Nano-Shield can penetrate - vehicles and buildings. Vehicles are expected to take advantage of the anti-heat properties of the solution. However, the product may meet stiff competition from tint. The product's main competitive advantage is that unlike tint, Nano-Shield coating is able to still transmit a larger portion of visible light through glass. This makes it easier for drivers of vehicles. Buildings take up the bulk of Nano-Shield demand due to the large areas of glass a single building can contain. Five market segments were then identified with each segment having a specific strategy for a ten-year planning horizon. The five market segments are construction companies, commercial buildings, restaurant and hospitals, residential buildings, and private and public vehicles. Demand forecasts show that an increase of 0.5% market share per year can be accommodated by Nano-Shield. The technical feasibility further shows that Nano-Shield can be manufactured in the right quality and quantity. The available technology was found adequate enough to mass-produce the solution in quantities that will meet its demand. Nano-Shield is expected to be sold as a product-service package. As such, company will employ workers in the production line and in the field. Production line workers were assigned to the manufacturing facility of the company situated in Mandaluyong City, Philippines. These workers will be expected to manufacture the solution and store it safely in containers. On the other hand, work teams will be deployed to the field in order to apply the solution on specific sites the customer may desire. The Nano-Shield company, once established, will be a corporation headed by a CEO. The company is estimated to have about 40 employees during its first five years. Finally investment on the Nano-Shield project was found to be acceptable and profitable by economic standards. The present worth of the project, within a five-year time horizon and with a discount rate of 14.76%, is Php 2,457,550.44. Aside from being a financially attractive investment, the project is also found to be socially attractive due to the employment, research development, and economic growth it can contribute to the Philippines. Furthermore, it was scientifically proven that the use of Nano-Shield can lessen the power consumption of air conditioners in buildings. Total energy savings for the whole NCR can reach up to 39,463.16 kWh by year 2018.